TRANSITION SIGNALS USED IN SHORT STORIES - Sahlan Tampubolon Tampubolon (English Education Department at FKIP Nommensen University, 2019)
The purpose of this study is to find out types and the dominant one of transition signals used in short stories. Research method used in this study is descriptive qualitative by doing library research. The data were collected by analyzing the transition signal used in five short stories. The results shows that the transition signals used in short stories are the transition signal indicates time, comparison, additional idea, and contrast. The dominant transition signal used is the transition signal indicates additional idea. The findings shows that the transition signal used on the five short stories is developed in a single central theme.